PROFIL CERITA UNTUK MENINGKATKAN KECERDASAN EMOSIONAL: APLIKASI ANCANGAN PSIKOLINGUISTIK - Subyantoro, Subyantoro (Kajian Linguistik dan Sastra, 2006)
This article aims to describe story profile which can improve emotional intellegence of cognate growth phase child of concrete operational. This Research subjek consist of: (a) cognate growth phase child of concrete operational and (b) narrator (in this case teacher). The Research was conducted in Semarang Town. The Instruments in this research are: (1) instrument to know story profile enthused by cognate growth phase child of concrete operational, (2) instrument to measure emotional intellegence of cognate growth phase child of concrete operational be- fore and after getting story based on figure function analysis at child story, (3) instrument to know executed narrating profile by narrator (teacher). Telling a story, based on figure function analysis in the reality can give picture and assist activity of telling a story that can develop emotional intellegence. The mentioned seen from tendency the increasing of emotional intellegence of child. Narrating execu- tion shall pay attention psychological aspect of child, including type, way of, theme, figure, path, and story background; existence of interaction braid in course of nar- rating between narrator and hearer; and giving of follow-up having a meaning of to child.Â Key words: children story, narrating, and emotional intellegence.Â